INFLUENCE OF LASER WELDING PARAMETERS ON THE CHARACTERISTICS OF JOINTS BETWEEN S355 CARBON STEEL AND 304 STAINLESS STEEL (Nonconventional Technologies Review, 2025)
Joining carbon steel S355 with stainless steel 304 is a common challenge in industrial equipment manufacturing, and laser welding presents itself as a modern technological solution with high potential. This unconventional technique offers significant advantages in terms of precision, speed, and process control. Our study aims to assess the feasibility of laser welding for these materials, focusing on determining the optimal process parameters. We analyzed how different parameters - such as laser power, pulse frequency, wire feed speed, and laser beam travel speed - affect the shape and depth of the weld bead. The experiments conducted demonstrated that variables such as laser pulse frequency, wire feed speed, and wire diameter play a crucial role in weld quality. We observed, for instance, that an excessive wire feed speed can lead to porosity in the weld seam. By identifying the optimal welding configuration, our work contributes to the development of efficient and reliable methods for joining these two types of steel, offering a high-performance alternative to conventional techniques.
Keywords: Laser welding; Carbon steel S355; Stainless steel 304; Welding parameters; Weld quality; Porosity